Implementasi Lintasan Belajar Menggunakan Cerita Dongeng pada Materi Pembagian di Sekolah Dasar - Apriani, Fitri; Lathiifah, Iis Juniati (Jurnal Pendidikan Matematika RAFA, 2021)
The aims of this study are to know the role of the learning path using fairy tales in mathematics learning in the division material. This study was using design research using the learning trajectory that was developed into a Worksheet where the research was conducted in three stages, namely the initial design, the teaching experiment (pilot experiment) and retrospective analysis. This research was conducted at SD Negeri 33 Pangkalpinang. The data were collected through several things, namely by pre-test and post-test, video recording, collection of student results, interviews, and field notes. The results showed that with the context of the Tiger, Buffalo, and Elephant Fairy Tales, students could understand the concept of division. Students are more interested and motivated in solving problems related to division so that learning is more meaningful. PMRI can be used as an approach to learning angle measurement in elementary schools.